The Childhood Executive Functioning Inventory (CHEXI): psychometric properties in a sample of Ecuadorian children - Tacuri-Reino, David (2024)
The Childhood Executive Functioning Inventory (CHEXI) is a widely used test in educational settings to identify deficits in Executive Functions (EF). This study aimed to adapt and evaluate the Spanish version of CHEXI in a sample of participants from Ecuador (n = 467). The study measured understanding using slightly different versions of the instrument, one initially administered to 373 participants and another withthree item changes used to assess 144 new participants. Cronbach’s alpha (α) and McDonald’s omega (ω) were used to assess internal consistency. Absolute (χ²/df) and incremental fit indices (CFI, TLI, SRMR,RMSEA) evaluated construct validity. The two-factor structure of CHEXI (Working Memory and Inhibition) was successfully replicated, demonstrating a good fit and high internal consistency. The Spanish version, with the two first-order correlated factors and modifications in items 10, and 22, was deemed suitable forassessing EF in children aged 8 to 12. We found that modifying the statements improved the instrument’s psychometric properties for Ecuador.